2021
DOI: 10.1007/s11356-021-14153-5
|View full text |Cite
|
Sign up to set email alerts
|

The associations between organophosphate esters and urinary incontinence in the general US population

Abstract: Organophosphate esters (OPEs) impact health in many ways. Since its relationship with urinary incontinence remains unknown, we aimed to explore their associations in the US general population. We combined the results of urine specimens test and self-reported urinary incontinence conditions from the National Health and Nutrition Examination Survey (NHANES) 2013–2014 among 2666 participants and then conducted linear regression and logistic regression to analyse associations between log2-transformed OPE concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…A recent analysis of the NHANES database by He et al (15) found that urine metabolites of OPEs were linked to a higher odds ratio for mixed incontinence in females. Nonetheless, the precise mechanism by which OPEs impact bladder function remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent analysis of the NHANES database by He et al (15) found that urine metabolites of OPEs were linked to a higher odds ratio for mixed incontinence in females. Nonetheless, the precise mechanism by which OPEs impact bladder function remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Then 0.2 mL of the subject's urine was used for enzymatic hydrolysis of urinary conjugates of the target analytes, automated off-line solid phase extraction, reversed phase high-performance liquid chromatography separation, and isotope dilution-electrospray ionization tandem mass spectrometry detection (29). We included four major OPE urine metabolites in this study (15): Diphenyl phosphate(DPHP), Bis(1,3-dichloro-2propyl)phosphate(BDCPP), Bis(2-chloroethyl) phosphate(BCEP), and Dibutyl phosphate(DBUP). According to the NHANES Analytic Guidelines, if the detection results of urine metabolites were below the limit of detection, the values were imputed by the square root of two.…”
Section: Urine Opes Metabolites Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several potential confounders were controlled for in the statistical model: age (years), sex (male or female), body mass index (BMI), race/ethnicity (Mexican American, Other Hispanic, non-Hispanic White, non-Hispanic Black, and Other race), poverty income ratio (PIR), family history of asthma (yes or no), serum cotinine (a biomarker of exposure to environmental tobacco smoke), and urinary creatinine. PIR was divided into three groups: ≤ 1.3, 1.3 to 3.5, ≥ 3.5, which representing low, medium, and high levels respectively (He et al 2022). For children in the same sex and age group, underweight/normal weight, overweight and obesity were de ned as BMI percentile < 85, 85 ≤ BMI percentile ≤ 95, BMI percentile > 95, respectively (Krebs et al 2007).…”
Section: Covariatesmentioning
confidence: 99%
“…This implies that changes in the endocrine state and inflammation can impact pelvic floor tissue structure, leading to urinary dysfunction. Besides, environmental factors, such as organophosphate esters with known endocrine-disrupting properties, are also linked to structural disruptions in the pelvic floor, contributing to incontinence [ 6 ].…”
Section: Introductionmentioning
confidence: 99%